High–dose density chemotherapy followed by simple trachelectomy: full-term pregnancy. Issue 6 (1st October 2008) - Robova, H.; Pluta, M.; Hrehorcak, M.; Skapa, P.; Rob, L.
Abstract : We report five patients with early-stage cervical cancer who do not fulfill criteria of fertility-sparing surgery (tumor more than 2 cm in the biggest diameter or infiltrating more than half of stroma). Five patients received three cycles of dose density neoadjuvant chemotherapy (NAC) at a 10-day interval: cisplatin plus ifosfamide in squamous cell cancer or plus doxorubicin in adenocarcinoma with good tolerance. After NAC, they underwent laparoscopic pelvic lymphadenectomy and vaginal simple trachelectomy. Two patients had no residual tumor, two had only microscopic residual disease, and one had macroscopic residual disease. Two women became pregnant 5 and 8 months after surgery, one delivered in term healthy baby and one is now in the second trimester of pregnancy without any complications. NAC followed by fertility-sparing surgery seems to be feasible treatment for women with tumor bigger than 2 cm or infiltrated more than half of the stroma.